Western Learned Magic as an Entangled Tradition Introduction - Otto, Bernd-Christian (Entangled Religions, 2023)
The introduction to this special issue outlines the concept of Western learned magic and suggests to analyse it as an entangled tradition, thus calling for an interdisciplinary, transcultural and transreligious perspective on its history. A working heuristic of seven different types of entanglement in the history of Western learned magic is proposed, whereas special emphasis is placed on processes of ritual hybridisation. Entangled rituals are one of the most unique characteristics of Western learned magic and often mirror millenia-long processes of textual-ritual transmission across numerous cultural and religious boundaries. Inspired by this working heuristic of different types of entanglement in the history of Western learned magic, the introduction summarises the six contributions to this special issue. These contributions represent the fruits of a workshop on Western learned magic as an entangled tradition that was held at the Center for Religious Studies (CERES) at the University of Bochum on September 14-15, 2019.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Entangled history; European history of religions; History of magic; ritual hybridity; Western esotericism; Western learned magic